Pembelajaran IPA Abad 21 dengan Literasi Sains Siswa - Scundy N. Pratiwi; Cari Cari; Nonoh Siti Aminah (Universitas Sebelas Maret, 2019)
In the 21st century, the development of science and technology in various countries increased rapidly. In response to this development, people are required to adapt in various aspects. One of them is the aspect of education that is very important for the progress of a country. In the aspect of education there are goals that directly affect the lives of students in making decisions based on information and their understanding, also called science literacy term. In Indonesia it is still low in achieving student science literacy. Good science literacy level can improve the quality of education so that it can compete with other countries in the era of globalization. With the new curriculum, the 2013 curriculum is expected to improve the quality of education in Indonesia. In the 2013 curriculum, scientific literacy is evident through scientific inquiry activities. Schools that have implemented the 2013 curriculum mean that only applying learning oriented to science literacy, have not been applied to the student evaluation stage. In a learning process will not be separated from the evaluation stage, while one of the tools used in the evaluation phase is a test. Scientific literacy evaluation instruments already exist and can be adopted from international research such as PISA, but the results of Indonesian students' science literacy in international studies apply generally. The method used in this paper is the study of literature. The results of the thinking in this paper is an evaluation instrument to measure the science literacy in the form of test questions. The purpose of this paper is: (1) To explain more about 21st century science lesson. (2) To explain more about the students' science literacy. (3) To explain more about science-based literacy evaluation tests.